Unusually broad-spectrum small-molecule sensing using a single protein scaffold - Hao Tian; Jesús Beltrán; Wesley George; Chase Lenert-Mondou; Norman Seder; Zoe I. Davis; Samuel D. Swift; Thomas Girke; Timothy A. Whitehead; Ian Wheeldon; Sean R. Cutler (Proceedings of the National Academy of Sciences, 2025)
Small-molecule sensing in plants is dominated by chemical-induced dimerization modules. In the abscisic acid (ABA) system, allosteric receptors recruit phosphatase effectors and achieve nM in vivo responses from µM receptor–ligand interactions. This sensitivity amplification could enable ABA receptors to serve as generic scaffolds for designing small-molecule sensors. To test this, we screened collections of mutant ABA-receptors against 2,726 drugs and other ligands and identified 553 sensors for 6.6% of these ligands. The mutational patterns indicate strong selection for ligand-specific binding pockets. We used these data to develop a sensor design pipeline and isolated sensors for multiple plant natural products, 2,4,6-trinitrotoluene (TNT), and “forever” per- and polyfluoroalkyl substances (PFAS). Thus, the ABA sensor system enables design and isolation of small-molecule sensors with broad chemical scope and antibody-like simplicity.